Evaluation of Erosion Rate With Small Plots and Usle Methods in Some Ultisol Soil Slope With Mixed Plants in North Tapanuli Siborongborong District - Mardohar Aritonang; Sumono Sumono; Lukman Adlin Harahap; Edi Susanto (Universitas Sumatera Utara, 2013)
Sloping land has a high erosion potential if converted to agricultural land without conservation measures. This study was aimed to measure erosion, determine tolerable erosion rate and Erosion Hazard Level (TBE) the Ultisol soil erosion using intercropping crop with peanuts and corn with slope of 9%, 19%, and 31% in July-October 2012 in the District Siborongborong using small plots and USLE predictions. The results showed that the amount of erosion using small plots for slope 9%, 19%, and 31% were 0,3 tons (ha.years)-1, 0.52 tons (ha.years)-1, and 0, 68 tons (ha.years)-1 respectively with low Erosion Hasard Level (TBE) category. USLE predictions based on 12 years of rainfall data for the slope of 9%, 19%, and 31% were 40.78 tons (ha.years)-1, 130.08 tons (ha.years)-1, and 312.78 tons (ha.years)-1 respectively with Erosion Hazard Level (TBE) category of moderate to very high. Predictions based on the USLE 4 months rainfall data for slope of 9%, 19%, and 31% were 1,02 tons (ha.years)-1, 3,28 tons (ha.years)-1, and 7,89 tons (ha.years)-1 respectively with low Erosion Hazard Level (TBE) category. The amount of tolerable erosion rate is 17,17 tons (ha.years)-1. Key words: Erosion, Ultisol Soil, Mixed Crops, Siborongborong